Lysosome-dependent cell death and deregulated autophagy induced by amine-modified polystyrene nanoparticles - Wang, Fengjuan (Open Biol, 2018)
Nanoparticles (NPs) typically accumulate in lysosomes. However, their impact on lysosomal function, as well as autophagy, a lysosomal degradative pathway, is still not well known. We have previously reported in the 1321N1 cell line that amine-modified polystyrene (NH(2)-PS) NPs induce apoptosis through damage initiated in the lysosomes leading ultimately to release of lysosomal content in the cytosol, followed by apoptosis. Here, by using a combination of biochemical and cell biological approaches, we have characterized in a mouse embryonic fibroblast cell line that the lysosomal alterations induced by NH(2)-PS NPs is progressive, initiating from mild lysosomal membrane permeabilization (LMP), to expansion of lysosomal volume and intensive LMP before the summit of cell death. Though the cells initially seem to induce autophagy as a surviving mechanism, the damage of NH(2)-PS NPs to lysosomes probably results in lysosomal dysfunctions, leading to blockage of autophagic flux at the level of lysosomes and the eventual cell death.